Analysis of Socioeconomic Status Among Risk Factors of Pediatric Abusive Head Trauma: A Systematic Review - Calista Felice; Muhammad Arifin Parenrengi; Prastiya Indra Gunawan; Wihasto Suryaningtyas (AKSONA, 2025)
Highlight: Most studies agreed that socioeconomic status (SES) influences the prevalence of pediatric abusive head trauma. SES is associated with other AHT risk factors and contributes to varied clinical outcomes. AHT incidence can be reduced by prevention strategies that focus on education and enhanced healthcare access.   ABSTRACT Introduction: Previous studies have shown that children from low socioeconomic status (SES) families are more likely to experience abusive head trauma (AHT). However, research on this topic remains limited. Some argue that clinicians may demonstrate diagnostic bias, tending to overidentify AHT in lower-SES children,  regardless of actual risk. Is low SES truly  a risk factor for AHT? If so, how does it affect AHT occurrence and its relationship with other risk factors? Objective: This review was to observe the relationship of SES as one of the risk factors of pediatric AHT. Methods: A systematic review was conducted on pediatric AHT using household SES data. Children with AHT were compared to non-abusive head trauma (non-AHT) controls. Articles published between  2002 and 2022 were searched from Scopus, PubMed, and Google Scholar, following PRISMA guidelines. Exlusion criteria included duplicates, inaccessible or non-English/Indonesia articles, and studies not meeting  PECO criteria. Data on child age, sex, type of head trauma, and SES were collected. Demographic characterisctics, SES, risk factors, outcome, and preventive measures were analyzed. Results: A total of 19,700 articles were found after searching Scopus, PubMed, and Google Scholar. After several screenings, 18 articles were included. Of the 18 articles, 17 included data on patients with AHT, and 6 included data on control patients. In total, there were 21,451 patients with AHT and 411,185 controls. The control group consisted of children with non-AHT and children without trauma. The mean, median , and standard deviation of the percentage of low SES patients with AHT were relatively higher than controls. A higher amount of articles agreed that SES had a significant impact. Conclusion: SES may influence pediatric AHT prevalence, but it should not be used as a determinant in diagnostic decision-making.